The Influence of Emotional Intelligence on Social Adjustments of Tenth Grade Students of SMA Unggul Negeri 2 Banda Aceh - Nurhasanah, Nurhasanah; Fitriana, Qonita (Jurnal Ilmiah Peuradeun, 2018)
Emotional intelligence is an individual’s ability to manage emotions by controlling the negative condition into a positive force and its relationship with social adjustment. In this case, the social adjustment in question is the adjustment of students in interacting with teachers, peers, and specific situations in the school environment effectively through the development aspects of self-awareness, emotional management, and utilization of emotions, empathy, and social skills. The purpose of this study was to describe the emotional intelligence and social adjustment variable of students as well as to determine how emotional intelligence influenced social adjustment of students. This research used a quantitative approach and ex-post facto method. The number of population was 118 students consisting of all tenth-grade students of SMA Unggul Negeri 2 Boarding School of Banda Aceh. Data were collected by using a closed questionnaire method with the scale 1-5. The data were processed and analyzed by using descriptive statistics and the coefficient of determination. The results showed that the influence of emotional intelligence on the social adjustment of students was 0,656 (coefficient of determination) that is 65%. Thus, it can be stated that Ha is accepted which means that emotional intelligence has a significant influence on the social adjustment of students.